2021
DOI: 10.1021/acs.analchem.1c02917
|View full text |Cite
|
Sign up to set email alerts
|

Fast 19F Magic-Angle Spinning Nuclear Magnetic Resonance for the Structural Characterization of Active Pharmaceutical Ingredients in Blockbuster Drugs

Abstract: Fluorinated drugs occupy a large and growing share of the pharmaceutical market. Here, we explore high-frequency, 60 to 111 kHz, 19 F magic-angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy for the structural characterization of fluorinated active pharmaceutical ingredients in commercial formulations of seven blockbuster drugs: Celebrex, Cipro, Crestor, Levaquin, Lipitor, Prozac, and Zyvox. 19 F signals can be observed in a single scan, and spectra with high signal-to-noise ratios can be acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…Numerical simulations indicate that δ-pulse RFDR at MAS frequencies of ∼25 kHz encodes both distance and tensor orientation, whereas finite-pulse RFDR (fpRFDR) at the MAS frequency of 60 kHz yields primarily distances, thus simplifying the analysis. These conclusions were similarly reached by Polenova and co-workers, who examined the effects of multispin 19 F- 19 F dipolar coupling and phase cycling on the performance of 19 F RFDR under 60–111 kHz MAS. , Using fluorinated aromatic compounds with defined distances, these authors found that fpRFDR efficiently transfers polarization without requiring large chemical shift differences. Application of this 19 F RFDR experiment to the HIV-1 capsid protein at 40 and 60 kHz MAS yielded cross peaks for fluorines separated by 9–23 Å, demonstrating the efficiency of 19 F RFDR spin exchange for distance measurement.…”
Section: Homonuclear 19f-19f Distance Techniquesmentioning
confidence: 57%
“…Numerical simulations indicate that δ-pulse RFDR at MAS frequencies of ∼25 kHz encodes both distance and tensor orientation, whereas finite-pulse RFDR (fpRFDR) at the MAS frequency of 60 kHz yields primarily distances, thus simplifying the analysis. These conclusions were similarly reached by Polenova and co-workers, who examined the effects of multispin 19 F- 19 F dipolar coupling and phase cycling on the performance of 19 F RFDR under 60–111 kHz MAS. , Using fluorinated aromatic compounds with defined distances, these authors found that fpRFDR efficiently transfers polarization without requiring large chemical shift differences. Application of this 19 F RFDR experiment to the HIV-1 capsid protein at 40 and 60 kHz MAS yielded cross peaks for fluorines separated by 9–23 Å, demonstrating the efficiency of 19 F RFDR spin exchange for distance measurement.…”
Section: Homonuclear 19f-19f Distance Techniquesmentioning
confidence: 57%
“…Next, we explored the application of T‐PADs in NMR studies of A 2A AR. Given the bio‐orthogonality and quantitative abundance of the natural isotopic fluorine atom, 19 F NMR has become the ideal approach in addressing GPCR diversity and dynamics [19,64–66] . 14M9G and 14M10M were chosen for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Given the bio-orthogonality and quantitative abundance of the natural isotopic fluorine atom, 19 F NMR has become the ideal approach in addressing GPCR diversity and dynamics. [19,[64][65][66] 14M9G and 14M10M were chosen for this study. 19 F-labelled A 2A AR samples were prepared by specifically introducing the probe 2,2,2-trifluoroethanethiol (TET) to selectively mutated Cys (A289 C) through in-membrane chemical modification.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…18,19 In particular, two-dimensional (2D) experiments such as 1 H-X (X= 1 H, 13 C, 14/15 N, 19 F, and 35 Cl) enabled the local structures and interactions in neat APIs and solid formulations to be elucidated. [19][20][21][22][23][24] One notable example is the use of 2D 14 N-1 H and 14 Nfiltered 1D 1 H and 2D 1 H-1 H correlation experiments coupled with spin-diffusion process for detecting APIs in solid formulations. 21,23 Using this approach, APIs can be selectively detected in tablet formulations.…”
mentioning
confidence: 99%
“…18,19 Specifically, 2D experiments such as 1 H-X (X = 1 H, 13 C, 14/15 N, 19 F, and 35 Cl) enabled the local structures and interactions in neat APIs and solid formulations to be elucidated. [19][20][21][22][23][24] One notable example is the use of 2D 1 H- 14 N and 14 N-filtered 1 H-1 H correlation experiments coupled with spindiffusion process for detecting APIs in solid formulations. 21,23 The proposed 2D 1 H-2 H iCOSY experiment operates in a manner akin to what is observed in 1 H- 14 N correlation experiments, nonetheless the H/D exchange of -NH n and -OH n manifests more 2 H sites to be excited and resolved in APIs.…”
mentioning
confidence: 99%